Implications Charismatic Leadership and Management Towards the Success of Islamic Educational Institutions - Nurisah, Nurisah; Muhammad, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Charismatic leadership and good management have long been considered key factors in the success of educational institutions. The success and failure of an institution are largely determined by these two factors. This study aims to analyze the relationship between charismatic leadership and management and its implications for the success of Islamic educational institutions. The method used in this study is a library research method by collecting data Through literature studies and information collected by researchers from various sources such as books, journal articles, and other sources of written information, this study finds that charismatic leaders with a clear vision, effective communication skills, institutional management with good management and high integrity can inspiring and motivating all school residents so that it has a positive impact on the performance of the institution. The positive impact produced by the charismatic leadership style is also able to attract public interest to make the institution he leads the right choice.